(untitled) (Journal of Social Sciences and Economics, 2024)
In recent years, the Ningxia Culture and Tourism Department has intensified online promotion efforts, leveraging influencers and new media to enhance local cultural and tourism publicity, achieving remarkable results. This study delves into the multifaceted influence of social media influencers on the tourism industry in Ningxia, China, analyzed quantitative tourism data from 2005 to 2023, employing a mixed-methods approach. Alongside influencer impact, our analysis encompasses variables such as the COVID-19 pandemic, tourist attractions, local businesses, and economic stability. We discovered that influencer-driven policies significantly bolster tourism traffic and economic gains, underlining the critical role of digital marketing strategies in regional tourism development. These findings offer actionable insights for destination marketing organizations and policymakers seeking to optimize tourism growth. Against the backdrop of Ningxia’s rich cultural heritage and scenic landscapes, this research elucidates the nuanced dynamics of influencer-driven tourism promotion in emerging destinations.